Epidemiology of recurrent seizure disorders and epilepsy in cats under primary veterinary care in the United Kingdom. (25th September 2020) - O'Neill, Dan Gerard; Phillipps, Stephanie A.; Egan, Jordon R.; Brodbelt, David; Church, David B.; Volk, Holger A.
Abstract: Background: Little epidemiological evaluation of recurrent seizure disorders in cats currently exists in veterinary literature. Objectives: To report the prevalence and risk factors for recurrent seizure disorders (RSD) and epilepsy in cats presented to primary care veterinary practices in the United Kingdom (UK). Animals: A total of 285 547 cats under veterinary care during 2013 presenting to 282 primary care clinics in the UK. Methods: Cohort study using multivariable logistic regression modeling for risk factor analysis. Results: There were 458 confirmed RSD cases, giving a 1‐year period prevalence of 0.16% (95% confidence interval [CI], 0.15‐0.18). A subset of 114 (24.89%) cases was recorded as having epilepsy, giving a 1‐year period prevalence of 0.04% (95% CI, 0.03‐0.5). Increasing age was significantly associated with increasing odds of RSD. Breed, sex, neuter status, and body weight were not associated with RSD. Epilepsy was most frequently diagnosed in adult to middle‐aged cats. Cats aged 3.0 to <6.0 years had 3.32 times higher odds of epilepsy diagnosis compared to cats <3.0 years of age. Insured cats were more likely to be diagnosed with epilepsy compared to noninsured cats. Conclusions and Clinical Importance: Although less common than in dogs, RSD and epilepsy still comprise an important disorder group in the UK cat population. Aging is a significant risk factor for these disorders in cats.